Analytical study of children outdoor playing environment - Mat Seman, Nurfatihah Anis; Abdul Rahman, Julaila; Kamaruddin, Zumahiran (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
All children deserve to be happy by exercising the right to play. Play is a process by which children learn and here it carries the meaning of a positive and beneficial play. Indeed, play is a biological necessity that teaches children the skills they will need in order to survive as adults and playing outside is of vital importance to children’s mental and physical health. The importance of an outdoor play area with numerous settings for play is accepted as the standard in the field of early child care and education development. Many researches have been done on children’s development and their interaction with outdoor environment. However, there is still no studies that compile all of research contents to obtain the studies trends, so that a direction on these issues can be seen clearly. This paper aimed to analyze the natural playground design element that can enhance children play experience. The data was collected using literature study and photo elicitation, on five(5) kinds of contents such as 1) children play behavior, 2) children play preferences and 3) children play experience, 4) design approach, 5) landscape components and elements. As the result, the lineup of research trends in five (5) contents as stated above were obtained. It can be said that the understanding on study trends on children outdoor playing environment will lead to the further information and discussion on children experience and behavior towards various types of play. In relation, the way of outdoor environment play a role to support the children’s physical, social skill and cognitive development is analyzed as well.